Cover Feature: Reduction Kinetics and Mass Transport of ZnO Single Entities on a Hg Ultramicroelectrode (ChemElectroChem 10/2020). Issue 10 (22nd April 2020) - Karunathilake, Nelum; Gutierrez‐Portocarrero, Salvador; Subedi, Pradeep; Alpuche‐Aviles, Mario A.
Abstract : The Cover Feature illustrates colloidal ZnO nanoparticles (10 nm diameter) that are electrolyzed in CH3 CN to make Zn(Hg). The stripping peak is proportional to the concentration of unsupported particles. The kinetic constant for ZnO reduction is determined from the electrolysis transient model, which is corrected for the delay induced by the potentiostat. Most reduction events happening within 100 ms, but consistent with mass transport studies more extended over experimental times. More information can be found in the Article by N. Karunathilake, S. Gutierrez‐Portocarrero et al .